Strategi Digital Marketing Tiktok Untuk Meningkatkan Brand Awareness Koding Next Surabaya - Agustin, Amanda Eka; Widayati, Yohana Tri; Prakoso, , Satrio Agung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In the digital era, social media marketing is crucial for enhancing brand awareness and expanding audience reach. TikTok has emerged as a popular platform among the youth, known for its creative and interactive content. Recognizing this potential, Koding Next Surabaya, a leading coding education institution for children and teenagers in Southeast Asia, aims to leverage TikTok to increase its brand awareness. Established in 2015 by Bartek Wasik and Mateusz Rybinski and present in Surabaya since 2022, Koding Next focuses on delivering top-quality programming education. This internship involves creating relevant content and studying innovative digital marketing strategies, particularly through interactive content and TikTok's promotional features, to reach a broader audience. This study seeks to develop an effective digital marketing strategy on TikTok, identify the most engaging content types, and measure the impact of TikTok's promotional features on brand awareness. The research focuses on the period from December to June, using metrics such as view count, engagement, and follower growth, within Surabaya's geographical context. The findings are expected to provide practical guidance for Koding Next Surabaya, enhance its brand awareness, and serve as a reference for future digital marketing research on TikTok.